2013
DOI: 10.3109/08923973.2013.864670
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional maturation of murine dendritic cells induced by 18 alpha- and beta-glycyrrhetinic acid

Abstract: Various studies have described glycyrrhizin (GL), an active triterpenoic saponin extract of licorice roots, as an anti-inflammatory, antiviral, antimicrobial, anti-tumor and immunomodulating agent. The activity of GL has been mainly attributed to its metabolites, 18-alpha (GA) and 18-beta-glycyrrhetinic acid (GB), which their mechanism of action on the immune system cells is not clearly known. In this study, we have investigated the effects of GA and GB on the immune system by targeting dendritic cells and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In addition, many studies have reported that the six active compounds listed in this paper, GL, GA, LCA, LCE, GLD and LTG, possess other activities. For example, GL and GA also have antitumor 39 , 40 , anti-inflammatory 41 , 42 , and immunoregulatory activities 12 , 43 , 44 . LCA, LCE, LTG and GLD also have inhibitory effects on diabetes 45 , 46 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies have reported that the six active compounds listed in this paper, GL, GA, LCA, LCE, GLD and LTG, possess other activities. For example, GL and GA also have antitumor 39 , 40 , anti-inflammatory 41 , 42 , and immunoregulatory activities 12 , 43 , 44 . LCA, LCE, LTG and GLD also have inhibitory effects on diabetes 45 , 46 , 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The roots and rhizomes are the main medicinal parts of licorice. Numerous studies have revealed many pharmacological activities of licorice, such as antiviral 4 , 5 , anti-inflammatory 6 , 7 , antitumor 8 , 9 , antimicrobial 10 , 11 and many other activities 12 , 13 . Among the pharmacological activities of licorice mentioned above, the antiviral and antimicrobial activities have been most commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently they have indicated that the extract of licorice roots containing 18-α and 18-β-glycyrrhetinic acid can increase DC maturation and modulate Th1/Th2 response through Th1 response enhancement, so licorice roots influence the host defense against infectious diseases. That's why it has shown anti-inflammatory, antiviral, antimicrobial, antitumor and immunomodulating activity in folk medicine [92].…”
Section: Curcuminmentioning
confidence: 99%
“…(93) Furthermore, liquorice extracts and their individual bioactive compounds provide several other health benefits for kidney, cardiovascular, immunological, respiratory, endocrine and central nervous systems which need to be underlined, since so far many physiological effects of liquorice on human body systems have been confirmed. (66,85,(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114) The health benefits of liquorice and its constituents have been suggested to be attributed to various physiological mechanisms, including modulation of vascular injury and atherogenesis, (111) inhibition of tyrosinase activity, (103) improvement of the brain energy supply, (110) increased glucose tolerance, (112) activation of the immune system, (101) protection against the oxidative stress of the liver, (95) memory enhancing effects (105) and improvement of the renal function. (114) Other physiological effects of liquorice on human body systems are presented in Table 2.…”
Section: Other Therapeutic Propertiesmentioning
confidence: 99%